Alfalfa Silage Treated With Sucrose Has an Improved Feed Quality and More Beneficial Bacterial Communities - Kang, Jinhe; Tang, Shaoxun; Zhong, Rongzhen; Tan, Zhiliang; Wu, Duanqin (Frontiers in Microbiology, 2021)
Alfalfa silage is one of the main roughages in the production of dairy cow, which can provide nutrition with high-quality to improve milk quality and production. Sucrose additions have been widely used to improve the silage quality. In this study, Tthe effects of sucrose on the fermentation quality and bacterial communities of alfalfa silage were investigated here using 0 %, 0.5 %, and 1 % sucrose ensiling treatments for 15, 30, and 60 d. The ensiling time significantly decreased the crude fiber content, and increased the ammonia nitrogen, acetic acid content, and the relative abundance of Enterococcus in the silages. The 1 % sucrose-treated silage at 60 d had the lowest neutral detergent fiber acid, acid detergent fiber, and crude fiber content and the highest relative feed value. Moreover, sucrose-treated silage contained less acetic acid, propionic acid, and butyric acid and had a lower pH than the controls for each duration. Enterobacteriaceae, Klebsiella and Enterococcus were the dominant genera in all groups, and the relative abundance of Enterococcus and Lactobacillus was higher in the 1 % sucrose-treated group than in the control. These results suggested that sucrose supplementation could improve alfalfa silage quality and increase its beneficial bacterial content.